2022
DOI: 10.3390/ijerph19127001
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Factors, Time of the Week, Physical Fitness and Saliva Cortisol: Their Modulatory Effect on Mental Distress and Mood

Abstract: Background: The purpose of the study was to assess the effect of diet quality and physical fitness on saliva cortisol, mood, and mental distress. These relationships were compared between a peak weekday (Wednesday) and a weekend day (Saturday) when mood may fluctuate. Methods: Forty-eight healthy college students participated in the study. Participants completed the Mood and Anxiety Symptom (MASQ) and Kessler Psychological Distress Scale 10 questionnaires on Wednesday and Saturday and recorded their diet for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Jacks et al [20] add some qualifiers to these results, as in their study it was only participants who exercised at a high intensity who significantly increased post-exercise salivary cortisol levels, and not those who exercised at a low or moderate intensity. Similar results were found by Begdache et al [59], who pointed out that cortisol level can be a gauge of workout intensity, since in their study, with a sample of 48 healthy college students made up of 23 athletes and 25 non-athletes who performed a cycling session at a minimum of 65% of age-adjusted maximal heart rate, the cortisol level increased only in the athletes. As the authors themselves suggest, this could be because the athletes performed the activity at a higher intensity than the non-athletes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Jacks et al [20] add some qualifiers to these results, as in their study it was only participants who exercised at a high intensity who significantly increased post-exercise salivary cortisol levels, and not those who exercised at a low or moderate intensity. Similar results were found by Begdache et al [59], who pointed out that cortisol level can be a gauge of workout intensity, since in their study, with a sample of 48 healthy college students made up of 23 athletes and 25 non-athletes who performed a cycling session at a minimum of 65% of age-adjusted maximal heart rate, the cortisol level increased only in the athletes. As the authors themselves suggest, this could be because the athletes performed the activity at a higher intensity than the non-athletes.…”
Section: Discussionsupporting
confidence: 87%
“…However, with their study using a cycloergometer intervention, Jacks et al [20] found that with a workout of less than 40 min there were no modifications in post-exercise cortisol levels. Other previously noted work carried out interventions that included VR+cycling of 12 [51], 20 [32], 50 [31] or 60 [59] min. This disparity in intervention durations and outcomes calls for protocols to be put in place, and for further research, not only to see to what degree duration affects physiological parameters, but also to analyze what type of exergame could be more effective in inducing changes to physiological markers.…”
Section: Discussionmentioning
confidence: 99%
“…Jacks et al (2002) add some qualifiers to these results, as in their study it was only participants who exercised at a high intensity who significantly increased post-exercise salivary cortisol levels, and not those who exercised at a low or moderate intensity. Similar results were found by Begdache et al (2022), who pointed out that cortisol level can be a gauge of workout intensity, since in their study, with a sample of 48 healthy college students made up of 23 athletes and 25 non-athletes who performed a cycling session at a minimum of 65% of age-adjusted maximal heart rate, the cortisol level increased only in the athletes. As the authors themselves suggest, this could be because the athletes performed the activity at a higher intensity than the non-athletes.…”
Section: Discussionsupporting
confidence: 84%
“…However, with their study using a cycloergometer intervention, Jacks et al (2002) found that with a workout of less than 40 min there were no modifications in post-exercise cortisol levels. Other previously noted work carried out interventions that included VR+cycling of 12 (Saiz-González et al, 2023), 20 (Jacks et al, 2002), 50 (Borg, 1982) or 60 (Begdache et al, 2022) min. This disparity in intervention durations and outcomes calls for protocols to be put in place, and for further research, not only to see to what degree duration affects physiological parameters, but also to analyze what type of exergame could be more effective in inducing changes to physiological markers.…”
Section: Discussionmentioning
confidence: 99%
“…CF represents individual attributes that are challenging to change, including personal character habits, values and physical quality. Previous research has shown that cortisol levels are in uenced by individual personality characteristics [48,49] and physical health [50,51], which helps explain the relationship between CF and hair cortisol concentration. Additionally, previous studies have demonstrated a negative correlation between t levels and burnout [52] and turnover contemplation [53], and a positive correlation with job satisfaction [54].…”
Section: Discussionmentioning
confidence: 99%